Epidemiological Situation on Plague around the World. Forecast of Epizootic Activity of Natural Plague Foci in the Russian Federation for 2024 - N. V. Popov; I. G. Karnaukhov; A. A. Kuznetsov; A. N. Matrosov; A. V. Ivanova; K. S. Martsokha; E. V. Kuklev; V. M. Korzun; D. B. Verzhutsky; E. V. Chipanin; A. V. Kholin; A. A. Lopatin; et al. (Проблемы особо опасных инфекций)
The aim of the review was to assess the epidemiological situation in natural plague foci in the Russian Federation, near and far abroad countries in 2023 and to forecast their epizootic activity for 2024. In 2023, cases of plague were registered in five countries worldwide: the Democratic Republic of the Congo (60 cases), the Republic of Madagascar (14), the United States of America (2), the People’s Republic of China (3), and Mongolia (5). A total of 84 cases of plague were recorded, of which 22 (26.2 %) were fatal. In the Russian Federation, in 2023, epidemic risks in epizootically active natural foci were significantly reduced due to the implementation of a set of preventive measures carried out by Rospotrebnadzor institutions, which was the guarantor of ensuring epidemiological well-being as regards plague. Plague epizootics were detected on the territory of two (Gorno-Altai high-mountain and Tuva mountain) out of 11 natural plague foci in the Russian Federation in 2023. Epizootics were reported on the territory of the Kosh-Agach district of the Altai Republic and the Mongun-Taiginsky kozhuun of the Tuva Republic. The total area of epizootics was 731.2 km2 (in 2022 – 248.3 km2). In total, 55 cultures of the antique biovar of the main subspecies Yersinia pestis pestis were isolated in 2023 (19 in 2022). The forecast for continuation of the tense epidemiological situation in the territory of the Altai and Tuva Republics in 2024 is substantiated. The trend of sustained growth in the epizootic potential of the East Caucasus high-mountain and Dagestan plain-piedmont plague foci is outlined. The prospects for introducing an automated electronic system for assessing the epidemic potential of natural plague foci into practice are explained.